Cultural Geometry. - Deitch, Jeffrey; Halley, Peter (Athene : Deste Foundation for Contemporary Art, 1988)
Armleder, John M. ; Artshwager, Richard ; Bickerton, Ashley ; Burton, Scott ; Dogg, John ; Dwyer, Nancy ; Fischer, R.M. ; Fritsch, Katarina ; Gobert, Robert ; Graham, Dan ; Halley, Peter ; Holzer, Jenny ; Kemps, Niek ; Klingelhöller, Harald ; Koons, Jeff ; Lemieux, Annette ; Levine, Sherrie ; Linke, Simon ; McCollum, Allan ; Merz, Gerhard ; Smithson, Robert ; Steinbach, Haim ; Trockel, Rosemarie ; Vaisman, Meyer ; Vercruysse, Jan ; Wallace & Donohue
Cultural Geometry, DEKA Foundation, House of Cyprus, Athene, January 18 to April 17, 1988
boek